2014
DOI: 10.2118/163839-pa
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Measurement of Hydraulic-Fracture Conductivities in the Barnett Shale

Abstract: Summary Horizontal wells that intersect multistage transverse fractures created by low-viscosity fracturing fluid with low proppant loadings are the key to revitalizing production from the Mississippian Barnett shale in the Fort Worth basin in Texas. However, direct laboratory measurements of both natural- and induced-fracture conductivities under realistic experimental-design conditions are needed for reliable well-performance analysis and fracture-design optimization. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 1 publication
2
31
0
Order By: Relevance
“…These effects are well known from previous experimental studies (e.g., Chen et al, 2015;Cuss et al, 2011;Engelder & Scholz, 1981;Guo et al, 2013;Kranz et al, 1990;McKernan et al, 2017;Tanikawa et al, 2010;Zhang et al, 2013Zhang et al, , 2015Zimmerman & Bodvarsson, 1996). In experiments designed to investigate the effect of low amplitude fluid pressure oscillations of seismogenic origin on permeability of Berea sandstone, Elkhoury et al (2011) andCandela et al (2015) reported permeability enhancements by up to 50% following fluid pressure oscillations of 20 s period for 3 min.…”
Section: Influence Of Hydrostatic Pressure-comparing the Three Rock Tmentioning
confidence: 54%
See 1 more Smart Citation
“…These effects are well known from previous experimental studies (e.g., Chen et al, 2015;Cuss et al, 2011;Engelder & Scholz, 1981;Guo et al, 2013;Kranz et al, 1990;McKernan et al, 2017;Tanikawa et al, 2010;Zhang et al, 2013Zhang et al, , 2015Zimmerman & Bodvarsson, 1996). In experiments designed to investigate the effect of low amplitude fluid pressure oscillations of seismogenic origin on permeability of Berea sandstone, Elkhoury et al (2011) andCandela et al (2015) reported permeability enhancements by up to 50% following fluid pressure oscillations of 20 s period for 3 min.…”
Section: Influence Of Hydrostatic Pressure-comparing the Three Rock Tmentioning
confidence: 54%
“…For example, Zhang et al (2013Zhang et al ( , 2015 used a standardized hydraulic flow cell to measure the normal stress dependence of fracture transmissivity over the range of reservoir pressures and temperatures and demonstrated the transmissivity-enhancing role of sand proppants (American Petroleum Institute industry-standard; API RP 61, 1989;API RP 60, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and modelling results usually show enhanced fracture closure rates at high closure stress and temperature, low Young's modulus and high amount of soft minerals, low fraction of proppants with small size, low fracture roughness and minor shear displacement (minor self-propping). The presence of water also accelerates the rate of fracture permeability reduction, in particular for clay-rich shales (Akrad et al, 2011;Alramahi and Sundberg, 2012;Guo and Liu, 2012;Kassis and Sondergeld, 2010;LaFollette and Carman, 2010;Liu and Sharma, 2005;Morales p [4] et Pedlow and Sharma, 2014;Reinicke et al, 2010;Stegent et al, 2010;Volk et al, 1981;Zhang et al, 2013;Zhang et al, 2015;Zhang et al, 2016b). The brittleness of shales, which correlates to some extent with their composition and elastic properties (Rybacki et al, 2016;Zhang et al, 2016a), may be also relevant for the long-term fracture healing rate.…”
Section: Introductionmentioning
confidence: 99%
“…According to the experimental results of Zhang et al [35], the relationship between the effective permeability and gas pressure can be written as:…”
Section: Gas Flow In Hydraulic Fracturementioning
confidence: 99%